How do Cochrane authors conduct web searching to identify studies? Findings from a cross‐sectional sample of Cochrane Reviews. (8th June 2020) - Briscoe, Simon; Nunns, Michael; Shaw, Liz
Abstract: Background: Searching the World Wide Web using search engines and websites can be conducted to identify studies for systematic reviews. When searching to support systematic reviews, the searcher faces challenges in using the basic search interfaces of most search engines and websites. Objectives: To describe and evaluate current practice of web searching in a cross‐sectional sample of Cochrane Reviews. The study also describes the stated aims of web searching, i.e. the identification of published or unpublished studies or both. Methods: A six‐month cross‐sectional sample of Cochrane Reviews was identified via the Cochrane Library. Reviews were inspected for detail about web searching. Findings were described and evaluated using a framework of key principles for web searching. Results: 423 Cochrane Reviews published August 2016–January 2017 were identified of which 61 (14%) reported web searching. Web searches were typically simplified versions of the bibliographic database search. Advanced and iterative approaches were not widely used. Google Search and Google Scholar were the most popular search engines. Most reports stated identification of grey literature as their aim. Conclusion: Basic web search interfaces necessitate simple searches. However, there is scope to use more diverse search features and techniques and a greater variety of search engines.